Pelabelan 0-Anti Ajaib dan 2-Anti Ajaib untuk Graf Tangga L - Quinoza Guvil -; Roni Tri Putra (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2016)
For a connected graph and a subset of . For a vertex the distance betwen and is . For an ordered k-partition of , the representation of with respect to is The k-partition is a resolving partition if are distinct for every The minimum k for which there is a resolving partition of is the partition dimension of In this paper will shown resolving partition of connected graph order where is a bipartite graph. Then it is shown dimension partition of bipartite graph, are pd(Kst)=n-1